Experimental investigation of closed loop spray cooling with micro- and hybrid micro-/nano-engineered surfaces. (5th November 2020) - Xu, Rui-Na; Cao, Lei; Wang, Gao-Yuan; Chen, Jian-Nan; Jiang, Pei-Xue
Highlights: A compact closed loop spray cooling system based on refrigeration cycle is built. Hybrid micro-/nano-engineered surfaces are investigated in closed loop spray cooling. CHF and HTC are improved by 59% and 42% respectively on the hybrid surfaces. Microstructures' size is varied and optimum value matches the droplet diameter. System efficiency is increased to 29.4% by hybrid micro-/nano-engineered surfaces. Abstract: With the urgent demands of ultra-high heat flux cooling technology, enhancement of spray cooling by surface structure as an effective thermal management method has drawn increasing attention. Combining micro- and nano-structures is a promising way to improve spray cooling but only a few attempts have been made, especially in an application oriented closed loop system. Here, spray cooling heat transfer of flat, rough, micro-structured and hybrid micro-/nano-structured surfaces are experimentally investigated in a closed loop spray cooling system based on R134a refrigeration cycle. The results show that compared with the flat surface, the rough heating surface, micro-structured surfaces and hybrid micro-/nano- engineered structures can increase the critical heat flux (CHF) by 15%, 42% and 59%, and heat transfer coefficient (HTC) of spray cooling system by 14%, 28% and 42%, respectively. The optimum characteristic size of micro structure is 200 μm, which corresponds to the mean droplet diameter. By combining this micro structure with irregular ZnO nanowires, the maximum CHF, HTC and system efficiency are obtained as 180 W/cm 2, 30 kW/m 2 K and 29.4%. The system combines the advantages of high cooling performance of spray cooling and the stable operation of refrigeration cycle. With closed loop experiments, the heat transfer enhancement by micro- and hybrid micro-/nano-structures is validated, and parametric influences as well as corresponding mechanisms are analyzed, which provide insights to guide industrial applications, and facilitate interdisciplinary study between advanced engineering materials and heat transfer to help expanding the frontier of spray cooling.